Just switch cot(x) = cos(x)/sin(x) Let u =sin(x)
you end up with ln|sin(x)| an eventually ln1 - ln(1/2) = ln1 - ln1 +ln(2)
as ln(1/2) = ln1 = ln(2) So B is the right answer
I ended up switching the cot to the inverse of tangent. Then I put in sines/cosine for tangent. I then did a trig substitution.
However, I end up with this:
ln1 is zero so I'm left with -ln(1/2).
The answer choices (this is mult.choice)
C. -ln(2-(sq.root of 3))
D. ln((sq.root of 3) -1)
E. None of the above
My answer key says A is the right answer, but I have NEGATIVE ln(1/2). I'm not sure where I went wrong. ??